Poor Pre-operative Nutritional Status Is a Risk Factor of Post-operative Infections in Patients With Gastrointestinal Cancer—A Multicenter Prospective Cohort Study - Zhang, Li; Wang, Siwen; Gao, Xuejin; Gao, Tingting; Huang, Lingli; Lian, Bo; Gu, Yingchao; Chen, Jianjiao; Guo, Dong; Jia, Zhenyi; Wang, Yong; Gong, Fangyou; et al. (Frontiers in Nutrition, 2022)
Objective: This study aimed to assess the prognostic value of the Nutritional Risk Score 2002 (NRS2002) and patient-generated subjective global assessment (PG-SGA) for postoperative infections in patients with gastric cancer (GC) and colorectal cancer (CRC) who underwent curative surgery. Methods: This prospective study included 1493 GC patients and 879 CRC patients who underwent curative surgery at 18 hospitals in China between April 2017 and March 2020. The NRS2002 and PG-SGA were performed on the day of admission. The relationship between the nutritional status of patients before surgery and postsurgical incidence of infection was analyzed using univariate and multiple logistic regression analyses. Results: According to NRS2002, the prevalence of nutritional risk was 51.1% in GC patients and 63.9% in CRC patients. According to the PG-SGA, 38.9% of GC patients and 54.2% of CRC patients had malnutrition. Approximately 4.4% of the GC patients and 9.9% of the CRC patients developed infectious complications after surgery. The univariate and multiple logistic regression analyses showed that the risk of infections was significantly higher in GC patients with a high nutritional risk score (NRS2002 ≥5) than in those with a low score (NRS2002 <3), and the PG-SGA score was identified as a predictor of postoperative infection complications of CRC. Conclusion: The preoperative nutritional status of patients with GC or CRC has an impact on postoperative infection occurrence. NRS2002 ≥5 was a risk factor for postoperative infection in patients with GC, and the PG-SGA B/C was a predictor of infections in patients with CRC.